Quantification of Micrornas by Absolute Dpcr for the Diagnostic Screening of Colon Cancer - E. Ahmed Farid; M. Gouda Mostafa; C. Ahmed Nancy; Hussein Laila (Journal of Colon And Rectal Cancer, 2019)
There is currently no validated micro(mi)RNA diagnostic stool test to screen for colon cancer (CC) on the market because of the complexity of fecal density, vulnerability of stool to daily changes, and the presence of three sources of miRNAs in stool (cell-free from fecal homogenates, exsosomal miRNAs from fecal exosomes, and fecal colonocytes). To address these complexities, we have first carried out a microarray miRNA experiment, using Affymetrix GeneChip miRNA 2.0 Arrays, on immunocaptured and enriched stool colonocytes of 15 subjects (three healthy controls and twelve colon cancer patients [three TNM stage 0-1 (e.g., polyps◻ ³ 1 cm, villous or tubvillous, or with high grade dysplasia), three stage 2, three stage 3, and three stage 4 in triplicates to select a smaller panel of 14 preferentially expressed mature miRNAs associated with colon cancer (12 Up-Regulated, miR-19a, miR-20a, miR-21, miR-31, miR-34a, miR-96, miR-106a, miR-133a, miR-135b, miR-206, miR-224 and miR-302; and 2 Down-Regulated, miR-143 and miR-145). In a subsequent validation study carried out on total small RNA extracted by immunocapture, followed by RT that employed TaqMan® miRNA Reverse Transcription (RT) Kit and a Custom TaqMan RT Primer Pool, absolute quantification of miRNAs, in copies/µl, was measured using a chip-based Absolute QuantStudio 3D Digital PCR analysis. To ensure that we have chosen human and not bacterial small total RNA, we have carried out coextraction protocols with E. coli K1 strain RS18, compare Agilent electrophoretic patterns, and also sequenced random samples throughout this research using mRNA/miRNA sequencing. Our initial quantitative dPCR miRNA data presented herein showe that the quantitative changes in the expression of a few mature miRNA genes in stool, which are associated with right and left colon cancer, would provide for a more convenient, sensitive and specific diagnostic screening markers thatare more useful than those test markers currently available on the market, such as the low-sensitivity (<15%) fecal occult blood test (FOBT); result in better compliance; and is more economical than the invasive and expensive colonoscopy exam in colon cancer, which can be cured if that cancer is detected at the early TNM stages, and that becomes incurable and deadly if not diagnosed before metastasis. Initial test performance characteristics of the miRNA approach showed that the test has a high numerical predictive value in colon cancer. Moreover, underpinning of the miRNA markers as a function of total RNA showed that the test can numerically differentiate between control subjects and colon cancer patients, particularly at the early stages of that curable cancer. We propose to extend our initial research results to a larger prospective and randomized five-years nested case-control study, to validate the expression of the above 14 miRNAs, in stool of 180 individuals in an epidemiologically designed study, using (30 controls and 150 colon cancer patients (thirty precancerous polyps (stage 0-1), forty five stage 2, and seventy-five colon cancer stages 3 or 4). chosen randomly by an epidemiological method from 900 control and CC subjects to allow for an adequate time to collect the required 900 stool samples, as well as allowing for statistically valid analysis, standardized test conditions, and to provide a mean for determining the true sensitivity and specificity of a miRNA-screening approach in noninvasive human stool. Power-analysis has indicated that a total of 180 individuals, which will take us 5 years to enroll in testing, is an appropriate number of subjects to standardize and validate our proposed miRNA screening test. We may find out at the end of the proposed validation study in stool that fewer miRNAs, or even one miRNA, may suffice to serve as an efficient and a quantitative marker for the non-invasive diagnostic screening of colon cancer in human stool. The above approach when combined with bioinformatics analysis, to correlate miRNA seed data with our previously published messenger (m)RNA target data in stool, allows for a thorough mechanistic understanding of how miRNA genes regulate mRNA expression, and would offer a better comprehensive diagnostic screening test for the non-invasive early detection stage (0-1) of colon cancer. In order to show the clinical sensitivity and specificity of the proposed miRNA test, the absolute miRNA PCR values, in copies/µl, will be correlated with FOBT, colonoscopy, and pathology data. Standardization will establish test’s performance characteristics (sample selection, optimal sample running conditions, preservation and storage) to ensure that the assay will perform the same way in any laboratory, by any trained personnel, anywhere in the World. Ultimately, a smaller number of selected validated miRNAs (<10) showing increased and reduced expression could suffice to give quantitative miRNAs colon cancer expression values, useful for the early diagnostic screening of that curable cancer.
Keywords: chips